NATURAL HERITAGE FOR US: SEBUAH STRATEGI DESTINATION BRANDING PARIWISATA PASCA BENCANA KABUPATEN ACEH JAYA - husna, asmaul; Fahrimal, yuhdi (SOURCE : Jurnal Ilmu Komunikasi, 2024)
As one of the areas devastated by the 2004 Aceh tsunami, Aceh Jaya Regency holds considerable potential for post-disaster tourism. However, post-disaster tourism literature has not been touched on by Aceh Jaya tourism researchers. Therefore, this study aims to analyze post-disaster tourism development in Aceh Jaya Regency, elaborated with destination branding and marketing communication approaches. Using a qualitative approach, we interviewed parties representing local government and tourism businesses. This research found that Aceh Jaya's tourism potential consists of (1) natural tourism, including rivers, islands, waterfalls, and beaches; (2) conservation tourism aimed at education and protection of turtle, elephant, and mangrove ecosystems; and (3) cultural tourism. Although there have been government efforts to develop leading destinations with the concept of 'natural heritage for us', several obstacles, such as the absence of an integrated tourist information center, limited promotion, uneven access and transportation facilities, and the lack of decent lodging, are obstacles to achieving the objectives of Aceh Jaya's tourism program. In the final section, we recommend strategies that the Aceh Jaya District Government can take to develop sustainable post-disaster tourism.